The theory of human act according to the Mu’tazilites - Abdull Rahman Mahmood,; Mohd Haidhar Kamarzaman, (Universiti Kebangsaan Malaysia, 2014)
The Mu’tazilites emphasizes the concept of Divine justice and the responsibility of man. According to them, Allah should reward or punish human beings according to their deeds. They maintain that man decides upon and creates his acts, both good and evil. He deserves reward and punishment in the hereafter for what he does. This article focuses on the arguments of Mu’tazilites in defending their theory. It also reveals their arguments in defending that human beings are the only authors of their own acts. The ‘Qiyas al-Gha’ib `ala al-Shahid’ has been widely used in their arguments.